Botrytis bunch rot on 'Sauvignon Blanc' grapevine on the Y-trellis and vertical shoot-positioned training systems - de Bem B.P.* (2017)
The objective of this work was to evaluate the effect of the Y-trellis (YT) and vertical shootpositioned (VSP) training systems on the incidence and severity of Botrytis cinerea, on cluster compactness, and total polyphenol (TP) contents of 'Sauvignon Blanc' grapevine (Vitis vinifera) in the municipality of São Joaquim, in the state of Santa Catarina, Brazil. Field trials were carried out in a randomized complete block design during the 2013/2014 and 2014/2015 crop seasons, with assessments performed at harvest. The YT system causes a higher incidence and severity of botrytis bunch rot under climatic conditions favorable to the pathogen, as well as greater cluster compactness, than the VSP system, without affecting the content of total polyphenols of 'Sauvignon Blanc' grapevine.